Sistema de monitoreo de polución de aire en los predios de la Universidad Técnica Estatal de Quevedo - Pérez García , Wilson Moisés (2024)
This project arises from the need to examine air quality, focusing specifically on the detection of gases such as carbon monoxide (CO), carbon dioxide (CO2) and propane gas, which are the target pollutant gases for this study. The relevance of detecting these gases lies in the significant risks they pose to human health, especially when there is prolonged exposure to significant levels of these pollutants for more than eight hours a day. This system will be integrated by nodes, which will consist of an esp8266 communication board, gas sensors of the MQ family, humidity and temperature sensors. The system will collect real-time data on air quality at the Manuel Haz Alvares campus, store them in a database, and then transmit them to a centralized platform. Through this platform, the university community can access updated information on air pollution levels and receive alerts in case dangerous concentrations of pollutants are detected. The main objective of the project is to provide information on how polluted the environment could become in a given time and to generate environmental awareness among the members of the university community, promoting more sustainable practices in environmental care. In addition, the system provides an invaluable tool for decision making.